Isotope-Dilution Gas Chromatography-Mass Spectrometry Method for the Selective Detection of Nicotine and Menthol in E-Cigarette, or Vaping, Product Liquids and Aerosols - Pérez, José J.; Watson, Clifford H.; Blount, Benjamin C.; Valentín-Blasini, Liza (Frontiers in Chemistry, 2021)
We developed a quantitative method for analyzing nicotine and menthol in e-cigarette, or vaping, products (EVPs). These products may adversely impact health through inhalational exposure to addictive and harmful chemicals. The presence of unknown substances in do-it-yourself e-liquids, counterfeits, or unregulated products may increase exposure to harmful chemicals, as underscored by the 2019 EVP use-associated lung injury (EVALI) outbreak. To minimize these risks, it is important to accurately quantify nicotine and menthol in e-liquids and aerosol emissions to evaluate EVP authenticity, verify product label accuracy, and identify potentially hazardous products. We developed a simple, versatile, high-throughput method using isotope-dilution gas chromatography-mass spectrometry for quantifying nicotine and menthol concentrations in both e-liquid contents and machine-generated aerosol emissions of EVPs. Rigorous validation has demonstrated that the method is specific, precise (CV<2.71%), accurate (percent error ≤7.0%), and robust. Linear calibration ranges from 0.01–1.00 mg/mL for both analytes was achieved, corresponding to expected analyte levels in e-liquids and machine-generated EVP aerosols. Limits of detection (LODs) in the final 10-mL sample extract were 0.4 µg/mL for nicotine and 0.2 µg/mL for menthol. The method was used to analyze aerosol emissions of 141 EVPs associated with the 2019 EVALI outbreak; detectable levels of nicotine (2.19–59.5 mg/g of aerosol) and menthol (1.09–10.69 mg/g of aerosol) were observed in 28% and 11%, respectively, of the samples analyzed. Nicotine was not detected in any of the tetrahydrocannabinol (THC), cannabidiol (CBD), or oil-based products, while menthol (2.95 mg/g of aerosol) was only detected in one of these products (THC-labeled). The analytical method can be used to quantify nicotine and menthol concentrations in the e-liquids and aerosols from a range of EVPs, and these findings highlight a difference between e-cigarette and other vaping products.